Construction of concrete structure (raft foundation) / Noor Shafrina Samsuri - Samsuri, Noor Shafrina (Universiti Teknologi MARA, Perak, 2014)
Foundation is a base of every building, importance structure to construct a building, structure and anything else. Therefore, this report will discuss about the construction of concrete structure which is raft foundation. Raft foundations are large slabs supporting a number of columns and walls under the entire structure. Raft slab is required when the allowable pressure is low or where the columns are spaced so close that the individual footings overlap. Raft foundations are useful in reducing the differential settlements and sustaining large variations in loads on the individual columns. In conventional analysis of raft foundation the reactive soil pressures due to the loads from the structure are not considered. This reactive pressure is important as the raft is subjected to bending due to loads from the structure and also from the reactive pressure offered by the soil. These effects considerably alter the forces and the moments in the structural members. This is where soil structure interaction comes into play. The effect of soil immediately beneath and around the structure, on the response of the structure when subjected to external loads is considered in soil structure interaction. In this case, the soil and structure are considered as components of one elastic system. During the analysis soil can be modeled using many soil models such as Linear elastic soil model, Winkler's soil model etc.